Effects of dental anxiety and anesthesia on vital signs during tooth extraction - Diya Zhang; Shenglai Li; Rui Zhang (BMC, 2024)
Abstract Background Anxiety is common preceding tooth extraction; hence, it is crucial to identify patients with dental anxiety (DA) and to manage DA. This study assessed the level of DA and influencing factors in tooth extraction patients in a dental hospital in China and changes in their blood pressure (BP) and heart rate (HR) during the tooth-extraction procedure. Methods The study was a cohort study. The Dental Anxiety Scale (DAS) was used to assess the level of DA of 120 patients before tooth extraction. A Demographics and Oral Health Self-Assessment Form was used to assess factors influencing DA. The correlations of DAS scores with HR and BP were measured. The effects of local anesthesia and general anesthesia on HR and BP were also compared using a Datex-Ohmeda anesthesia monitor to detect HR and BP continuously before and after anesthesia. Independent sample t-tests, OLS multiple regression model and one-way analysis of variance were applied to analysis the results. Results Based on the DAS score, 12.5% of the participants were identified as suffering from DA. DA was related to age, gender, and the self-assessment of oral health. The DAS score was correlated with increased BP (P < 0.05). BP showed an overall upward trend after local anesthesia, while it was generally stable after general anesthesia. The systolic BP at 4 and 5 min and the HR at 2 and 4 min increased remarkably (P < 0.05) after local anesthesia compared with those before anesthesia. The HR and BP of patients under local anesthesia were generally higher than those of patients under general anesthesia were during the operation. Conclusions The prevalence of DA in adults was 12.5% in this study population. DA was related to gender, age, and the self-assessment of oral health. The score of DAS was correlated with BP. Compare to local anesthesia, general anesthesia can make the vital signs of tooth extraction patients more stable.